2020
DOI: 10.3390/ijgi9110617
|View full text |Cite
|
Sign up to set email alerts
|

A New Urban Vitality Analysis and Evaluation Framework Based on Human Activity Modeling Using Multi-Source Big Data

Abstract: A quantitative study of urban vitality brings new insights for evaluating the external construction environment and internal development power of cities. However, it still has limited knowledge of the relations between people’s diverse urban life and urban vitality, although urban activities are often used as the proxy for urban vitality. This paper aims to deeply mine the content of urban social life and reveal the driving mechanism of urban vitality after inspecting human activities. We propose a general fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 53 publications
(43 reference statements)
1
42
0
Order By: Relevance
“…For DPTS, a strong negative effect can be observed in the central regions (Hexi and Jiangbei), demonstrating that these regions have more convenient public transport, and then higher urban vitality. A study by Liu et al [71] also showed that traffic access and land use mix have strong positive correlations with urban vitality in the central area rather than peripheral area. Besides, our findings suggest that the DS has positive associations with urban vitality in urban waterfronts, especially in the central regions (Hexi and Jiangbei), demonstrating that the more proximity to the shoreline, the lower urban vitality.…”
Section: The Influencing Of Built Environment Characteristics On Urban Vitality In Urban Waterfrontsmentioning
confidence: 94%
“…For DPTS, a strong negative effect can be observed in the central regions (Hexi and Jiangbei), demonstrating that these regions have more convenient public transport, and then higher urban vitality. A study by Liu et al [71] also showed that traffic access and land use mix have strong positive correlations with urban vitality in the central area rather than peripheral area. Besides, our findings suggest that the DS has positive associations with urban vitality in urban waterfronts, especially in the central regions (Hexi and Jiangbei), demonstrating that the more proximity to the shoreline, the lower urban vitality.…”
Section: The Influencing Of Built Environment Characteristics On Urban Vitality In Urban Waterfrontsmentioning
confidence: 94%
“…To explore the spatial pattern and driving mechanism of UV, a conceptual framework has been proposed by [19], in which big data (e.g., internet sharing data and geospatial data) and the GWR (geographically weighted regression) are integrated. Consistent with the GMUV in this paper, high environment quality, manifested by things such as high road density, has a strong effect on economic vitality.…”
Section: Understanding Uv Through the Gmuvmentioning
confidence: 99%
“…From the physical environment, the road density contributes greatly to the EnV, and further to UV. High road density indicates a good accessibility to public space, which is conducive to gatherings of people and promoting EcV and SV [19]. The study area (200,000 km 2 ) covers 140 districts and counties, among which most of them have low road density which has limited the communication between people, capital, and information.…”
Section: Suggestions For the Development Of The Study Areamentioning
confidence: 99%
See 2 more Smart Citations